The Effectiveness of Legal Aid Implementation under PERMA No. 1 of 2014 in Religious Courts: A Policy Analysis Using Van Metter and Van Horn’s Framework (Program Studi Hukum Keluarga Islam, 2025)
This study aims to analyze the implementation of Supreme Court Regulation (PERMA) Number 1 of 2014 on Legal Aid Posts (Posbakum) in Religious Courts, using an empirical juridical research design and a regulatory-statutory approach. Primary data were collected through observations and interviews with judges, Posbakum officers, and the community as service recipients at the Palu Religious Court. The results of the study indicate that the implementation of Posbakum services at the Palu Religious Court has been running in accordance with PERMA provisions, marked by an increase in the number of legal aid service recipients. Through an analysis of the policy implementation model by Van Metter and Van Horn, it was found that successful implementation was supported by clear standards and targets, structured cooperation agreements, community support, and positive attitudes of implementers. However, there are still obstacles on the limited budgets and inadequate service room facilities, affecting the effectiveness of providing legal aid to the community